Facile Gram‐Scale Synthesis of the First n‐Type CuFeS2 Nanocrystals for Thermoelectric Applications. Issue 25 (3rd July 2017) - Gabka, Grzegorz; Zybała, Rafał; Bujak, Piotr; Ostrowski, Andrzej; Chmielewski, Marcin; Lisowski, Wojciech; Sobczak, Janusz W.; Pron, Adam
Abstract : The described method enables facile gram‐scale preparation of CuFeS2 nanocrystals exhibiting interesting thermoelectric properties from simple and readily available precursors. Exchange of primary organic ligands for inorganic ones using either (NH4 )2 S or triethyloxonium tetrafuoroborate (Meerwein's salt) resulted in nanocrystals from which n‐type bulk thermoelectric materials were obtained through sintering under pressure. The measured physical properties of the fabricated bulk thermoelectric materials depend on the type of inorganic ligands used for the exchange. In particular, materials that were surface‐modified with Meerwein's salt have a higher Seebeck coefficient (| S | = 238 µV K –1 ) as compared to those modified with (NH4 )2 S, whereas the latter exhibit higher electrical conductivity (8500 S m –1 ) and lower thermal conductivity (0.5 W m –1  K –1 ), both of which are favorable for thermoelectric applications. Abstract : We have elaborated a gram‐scale preparation of ternaryCu‐Fe‐S nanocrystals, which can be used as components of n‐type thermoelectric materials.